Tasawuf Sebagai Basis Tasamuh - Said Aqiel Siradj (AL-TAHRIR, 2013)
Abstract: This article tries to analyze the articulation of tasa>muh} as any form of recognition of difference. Tasa>muh} can exist if there is recognition of the diversity of thought. Therefore, the existence of tasamuh can be meaningful if it is present in a pluralistic reality. On the other hand, the articulation of tasa>muh} can also be presented from the values of sufism, namely by putting the reality of God as a mirror of life. Phenomena of the universe is the God’s manifestation. Therefore, all the phenomena of nature is already acknowledged its existence by God, because He created it. Then, when the articulation Tasamuh presented through this understanding, then it can be a social capital in order to build a more moderate social order.